A study on investigating the effect of lignosulfonate-based com-paction aid admixture dosage on the properties of roller com-pacted concrete - Gok, Saadet Gokce; Kilic, Ismail (Revista de la Construcción. Journal of Construction, 2022)
In this study, roller compacted concrete was produced by using a modified lignosulfonate-based chemical admixture which is suitable for use in wet, semi-dry or zero slump concrete, and the effect of admixture dosage on the physical and mechanical properties of the concrete was investigated. In the production of roller compacted concrete, the cement content was 300 kg/m3 and the chemical admixture dosages have been changed as 0%, 0.3%, 0.6% and 0.9%. Percentage of compactibility, total water absorption, unit weight, ultrasonic pulse velocity, dynamic modulus of elasticity, concrete compressive strength at the ages of 3 and 28 days were determined for the roller compacted concrete specimens. Roller compacted concrete with the lowest percentage of water absorption, the highest percentage of compactibility, ultrasonic pulse velocity, compactness, compressive strength and dynamic modulus of elasticity was the concrete produced with 0.6% admixture dosage. With the concrete design and the chemical admixture in question, it has been observed that the optimum dosage of chemical admixture for the production of the best quality concrete in terms of the concrete properties examined was 0.6%.